UPAYA MENINGKATKAN HASIL BELAJAR IPA TENTANG KOMPONEN EKOSISTEM MELALUI MODEL GALLERY WALK DI SISWA KELAS V SD INPRES OETETE 2 KUPANG - Ande, Andreas; Lehan, Andriyani A. D.; Bria, Yanuaria Hoar (Universitas Nusa Cendana, 2023)
The aim of the research is to determine the application of the gallery walk learning model to improve learning outcomes. the research method used in the research is classroom action research (PTK) This research consists of several stages, namely planning, implementing actions, observing, and reflecting. in this study, the data analsis techning used by researchers for this research was to find the average student learning outcomes through observation sheets and tests in class on researcts subjects totaling 25 students, with details of 12 male students and 13 female students. The research results show that: 1) the application of the gallery walk learning model in science learning abaut ecosystem components in class V of SD Inpres Oetete 2 Kupang can ben sai to be successful in the very good category. this category can be proven by the results of observasi teacher activities whict got a score of 78,75% (good) in the first cycle, increasing to 93,5% ( very good) in cycle II, while the results obtained a score of 68% (fair) in cycle I and increased to 85,7 % (very good) student learning in this study also experienced an increase in the good category. is known from the percentage of student learning completeness. in cycle I it was 36% (very poor) increasing to 92% (very good) in cycle II